Shaping the future of translation careers: Student interest and the need for curriculum reform in the AI era - Humanika, Eko Setyo; Radjaban, Yohanes (Universitas Ahmad Dahlan, 2024)
This study explores students’ interest in pursuing a career in translation in the rapid advancement of artificial intelligence and the growing need for translation curriculum reform. A mixed method was employed, involving 45 students from the English Literature Department at the University of Technology Yogyakarta (UTY) during the 2023-2024 academic year. Participants were selected using a stratified random sampling technique and included second-, third-, and fourth-year students. Data collection was conducted through questionnaires and semi-structured interviews. The questionnaire assessed students’ interest in translation careers, while the interview provided deeper insight, involving six respondents from the three batches, representing both positive and negative responses to the questionnaire items. The findings indicate that 26,6% of respondents are interested in a translation career, 55,6% are neutral, and 15,53% are not interested. Neutral responses were most common among second-year students and least common among fourth-year students, likely because higher-year students tend to focus more on career planning. The study also highlights the need to reform translation curricula by integrating machine translation into classroom instruction, as a computer assisted as well as automatic. The findings of this study suggest the need for further research on developing an AI-based model for teaching translation.